Curricular Change in Response to Changing Demands: Experience from Saskatchewan - Eric Micheels; Robert Roy (Journal of International Agricultural and Extension Education, 2026)
At the University of Saskatchewan, the B.Sc. in Agribusiness was first offered in 2006 in response to growing demand from both students and industry for a program that provided different tools than a traditional agricultural economics degree. Following the introduction of the B.Sc. in Agribusiness degree, enrollment numbers have grown steadily, and job placements have continually been high. While this would seem to indicate that the program is meeting needs of both students and industry, recent survey data from the College of Agriculture and Bioresources suggests that there continue to be areas where the program could be improved. In this paper, we outline our learner-centered approach to curriculum innovation that led to the development of different learning pathways within the B.Sc. in Agribusiness degree. Through this process, we aimed to re-imagine what the B.Sc. in Agribusiness should look like for stakeholders in western Canada while still ensuring that the program still achieves the learning outcomes in line with those proposed by Gillespie and Bampasidou (2018).
Keywords: Agribusiness; curriculum review; employer feedback; program emphasis